Citra Positif Hijab Pada Iklan Televisi (Studi Makna Semiotika Pesan Non Verbal Pada Iklan-Iklan Versi Model Berhijab) - Sofyan Rizal (STID DI AL-HIKMAH, 2017)
This study contains the analysis of semiotic meaning of nonverbal messages in ad Osmo edition Filter Sariwangi tea, cosmetics advertising Fair & Lovely edition S2 and marriage and soap ad Lifeboy Hijab edition. This study focused on non-verbal signs that include kinesik messages are divided into pasial message, gestural and postural. The research method uses a qualitative description of the method of data analysis techniques using semiotic analysis Sande Charles Peirce. These results indicate that the message signs contained in the three ads above contain elements of nonverbal language in it. Ads Tea Sariwangi Osmo edition Filter has been able to convey nonverbal messages that can be understood generally that the housewife who hijab has a positive image is that he is a loving mother figure, humble, motivator and problem solver. Through the concept of nonverbal messages advertising Advertising Cosmetics Fair & Lovely S2 and Marriages edition contains a positive image of women hijab that niqab women should have strong principles in determining the future of their education and career. Likewise in advertising Advertising Soap Lifeboy Hijab issue veiled Muslim woman image has a strong character in Islamic education in the family and be able to build good interpersonal communication and effective with their children in educating and mentarbiyah.